Novel tubular constructs for urinary diversion: a biocompatibility study in pigs. (16th February 2016) - Sloff, Marije; Simaioforidis, Vasilis; Geutjes, Paul J.; Hoogenkamp, Henk R.; van Kuppevelt, Toin H.; Daamen, Willeke F.; Oosterwijk, Egbert; Feitz, Wout F.
Abstract: The use of bowel tissue for urinary diversion can be associated with severe complications, and regenerative medicine may circumvent this by providing an engineered conduit. In this study, a novel tubular construct was identified for this purpose. Three constructs (diameter 15 mm) were prepared from type I collagen and either (a) a semi‐biodegradable Vypro II polymer (COL–Vypro), (b) a rapidly biodegradable Vicryl polymer (COL–Vicryl) or (c) an additional collagenous layer (COL–DUAL). After freezing, lyophilization and crosslinking, all constructs showed a porous structure with a two‐fold higher strength for the polymer‐containing constructs. These constructs were connected to full bladder defects of 11 female pigs and evaluated after 1 ( n  = 4) or 3 months ( n  = 5). With respect to surgical handling, the polymer‐containing constructs were superior. All pigs voided normally without leakage and the survival rate was 82%. For the implanted COL–Vypro constructs (8/9), stone formation was observed. COL–DUAL and COL–Vicryl showed better biocompatibility and only small remnants were found 1 month post‐implantation. Histological and immunohistochemical analysis showed the best regeneration for COL–Vicryl with respect to urothelium; muscle pedicles and elastin formation were best developed in the COL–Vicryl constructs. In this study, COL–Vicryl constructs were superior in both biocompatibility and bladder tissue regeneration and have high potential for artificial urinary diversions. Copyright © 2016 John Wiley & Sons, Ltd.